2016
DOI: 10.3233/bmr-160676
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic peripheral neuropathy: Correlation between nerve cross-sectional area on ultrasound and clinical features

Abstract: US is a sensitive diagnostic technique for detecting DPN; however, it does not indicate disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
5
21
2
Order By: Relevance
“…Our result seems conflicting with previous studies that have demonstrated peripheral nerve enlargement in patients with diabetic peripheral neuropathy . We do not have an exact explanation for this but may be peripheral nerve neuropathy and cranial nerve neuropathy have different pathogenesis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our result seems conflicting with previous studies that have demonstrated peripheral nerve enlargement in patients with diabetic peripheral neuropathy . We do not have an exact explanation for this but may be peripheral nerve neuropathy and cranial nerve neuropathy have different pathogenesis.…”
Section: Discussioncontrasting
confidence: 99%
“…It had been validated in cases of entrapment neuropathies and recently has been investigated in more generalized neuromuscular disorders . Of interest, enlargement of peripheral nerves has been noted in some studies in patients with diabetes . A logical next step is to investigate its role in the evaluation of the cranial nerves.…”
Section: Introductionmentioning
confidence: 99%
“…With advances in ultrasound technology in recent years including probes with higher frequency and better resolution, it has become possible to visualize internal structures such as the epineurium, perineurium, and nerve bundles with a diameter of ≤0.5 mm as well as some small nerves and cutaneous nerves. Thus, HFU provides valuable morphologic information that can complement electrophysiologic data [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al evaluated the feasibility of CSA at the wrist of 30 DPN vs. 32 healthy controls and found a strong ICC reliability of interobserver (0.998) and intraobserver (0.995) examinations . However, for diagnostic accuracy, studies have shown that nerve ultrasound is unable to distinguish between varying severities of DPN …”
Section: Discussionmentioning
confidence: 99%